Benchmarking of neurosurgery training in Pakistan - Ali, Noor-Ul-Ain; Ali, Syed; Sharif, Salman; Amin, Faridah (Asian Journal of Neurosurgery, 2021)
Introduction: Neurosurgery is a challenging field of surgery. A neurosurgeon has to be trained with the finest skills, knowledge, and competencies necessary to provide high-quality patient care. Maintaining postgraduate training standards is a challenge in Pakistan due to low budget allocation to the health sector. This study aims to assess the difference in parameters among different institutes in different sectors and provinces offering neurosurgery training in Pakistan. Methods: A nationwide survey was conducted by the Neurosurgery Department at Liaquat National Hospital Karachi, from November 2019 to February 2020. Data were collected through a questionnaire from neurosurgery trainees from all over the country. The questionnaire was divided into the following sections: Sociodemographics and infrastructure of training site, clinical skills training and exposure, knowledge-based education, and workload. The data were kept confidential and institutional names were not inquired or disclosed. Results: The response rate was 85.3% (151/177), with more males (80%) than females. The total number of trainees was higher in government than private institutions (P < 0.005). The frequency (P = 0.030) and number of trainees (P < 0.005) inducted per cycle was more among government institutions. Participation in international conferences was higher among trainees in private sector (P = 0.006). The frequency of clinics was significantly higher in private institutions (P < 0.005), though the number of patients seen per clinic was lower than in government sector (P < 0.005). At a provincial level, there was a significant difference in gender distribution (P = 0.020), total number of trainees (P < 0.005), number of residents per induction (P < 0.005), frequency of mortality and morbidity meetings (P < 0.005), morning meetings (P < 0.005), number of calls per week (P < 0.005), number of workshops attended (P < 0.005), exposure to radiation (P = 0.003), frequency of outpatient departments (OPDs) attended per week (P = 0.002), and number of patients seen per OPD (P 0.02). Conclusion: This study reported variability in the quality of neurosurgery training programs within public and private sector with even greater differences between the four provinces of Pakistan. We recommend continuous assessments and re-accreditation of these training programs through subject experts and health-care educationists to improve the quality of training programs; hence the quality of service and patient care.
Keywords: Accreditation council for graduate medical education; college of physicians and surgeons Pakistan; khyber Pakhtunkhwa; outpatient department